Relationship between Mother Characteristic and Anemia in Pregnant Women at Puskesmas Ikua Koto - Faisal, Afrah Diba; Suryanis, Ira (JURNAL IBU DAN ANAK, 2022)
In Indonesia, the prevalence of anemia in pregnancy is still high, namely around 89.6% of the total number of pregnancies of 1.5 million pregnant women. This study aims to determine the relationship between maternal characteristics and the incidence of anemia in pregnant women in the area of ​​the Ikua Koto Health Center in Padang City in 2022. The type of research is analytic which was carried out at the Ikua Koto Health Center in Padang City from April 1 to 30 2022 with a total of 70 respondents. . Sampling was carried out by accidental sampling technique using a questionnaire as a research instrument, the data was processed univariately and bivariately with the Chi squere test. The results of the study showed that most of the respondents had anemia in pregnant women. There was no significant relationship between education level, employment status, parity, and level of knowledge with the incidence of anemia in pregnant women. It is hoped that health workers, especially health workers, in carrying out health promotion for pregnant women will place more emphasis on the changes that occur in pregnant women, especially the promotion of anemia in pregnant women.